Squamous Papilloma of Urinary Bladder in a Chronic Smoker - S. Muqqurab Ali Khan; P. Vamsi Krishna; Keerthana Kota; C. Nithish (Current Innovations in Medicine and Medical Science Vol. 5, 2022)
Squamous cell papilloma lesions of the urinary bladder are very rare. We describe a case of 56-year-old male patient with benign squamous cell papilloma. Histologically, the lesion showed papillary processes with central fibrovascular cores which were lined by hyperplastic benign squamous epithelium. No nuclear atypia or koilocytic dysplasia or stromal invasions were seen and the diagnosis of Squamous papilloma was established. These lesions are extremely rare, and even though they are considered benign, and non-HPV related, the patient should be on surveillance for the recurrence of low-grade urothelial carcinoma.